From Theory to Action: Bridging Governance Gaps in Public Policy for Sustainable Development - Saddam Rassanjani; Nitiwate Meesonk (Journal of Contemporary Governance and Public Policy, 2025)
Public policy addresses societal challenges, shapes governance structures, and enhances institutional performance. This paper critically reviews the stages of the policy process—formulation, implementation, and evaluation—by examining key theoretical frameworks, including the policy cycle, rational and incremental models, and evidence-based policy-making. While these frameworks offer valuable foundational insights, their practical application is often constrained by complex political, institutional, and socio-cultural factors. The analysis underscores how real-world governance dynamics frequently demand adaptive and participatory approaches that extend beyond the linear logic of conventional policy models. Drawing on a qualitative literature review, the study emphasises the growing relevance of Sustainable Development Goal 16 (Peace, Justice, and Strong Institutions) as a normative foundation for effective governance. SDG 16 advocates inclusive institutions, accountable decision-making, and equitable access to justice—principles closely aligned with effective public policy. By integrating governance-oriented considerations such as transparency, stakeholder engagement, and institutional resilience, the paper argues for a more flexible and context-sensitive approach to policy-making. The findings suggest that bridging the gap between theory and practice requires methodological pluralism and a commitment to institutional values consistent with the spirit of SDG 16. This article contributes to a deeper understanding of how public policy can strengthen democratic governance in an era of uncertainty and complexity.